Pengaruh Intellectual Capital dan Rasio Aktivitas terhadap Kinerja Keuangan pada Perusahaan Sektor Perbankan yang Tercatat di Bursa Efek Indonesia Tahun 2019-2024 - Putu Giano Artanaya; Ni Wayan Yulianita Dewi; Putu Riesty Masdiantini (Vokasi : Jurnal Riset Akuntansi, 2026)
The study aims to analyze the effect of intellectual capital and activity ratios on the financial performance of banking sector companies listed on the Indonesia Stock Exchange during the period 2019-2024. The variables used in this study are: (1) independent variables, which consist of intellectual capital and activity ratios; and (2) the dependent variable, which is financial performance. The research approach employed is a quantitative research method. The population in this study consists of banking companies listed on the Indonesia Stock Exchange during the 2019-2024 period, totaling 47 companies. The sample selection process used purposive sampling, resulting in 30 selected companies as the research sample. The analytical technique used is multiple linier regression analysis. The results of the study indicate that: (1) intellectual capital has a positive and significant effect on the financial performance of companies; and (2) activity ratios also have a positive and significant effect on the financial performance of companies.